Experimental aerodynamic control of a long-span suspension bridge section using leading- and trailing-edge control surfaces - Gouder, K; Zhao, X; Limebeer, D; Graham, J (Institute of Electrical and Electronics Engineers, 2015)
We experimentally investigate the suppression of flutter in long-span suspension bridges. A rigid sectional model of a long-span suspension bridge is mounted in a wind tunnel on a suspension system. Control surfaces, which are used to suppress flutter, are movable flaps that are fitted to the bridge section's leading and trailing edges. The flaps are responsive to the deck's heave and pitch motions. In this paper, the aerodynamic force is modeled using a thin aerofoil theory, although other modeling techniques can be used. The controller has a second-order passive transfer function with inputs of a combination of the deck's pitch angle and heave position, and outputs of the flaps' angular positions. The control system design problem is solved as an Ɦ∞ optimization problem.